One new lignan and one new fluorenone from Dendrobium nobile Lindl. (August 2021) - Cao, Xue; Yang, Li; Dai, Hao-Fu; Wei, Yan-Mei; Huang, Sheng-Zhuo; Wang, Hao; Cai, Cai-Hong; Wang, Ling; Mei, Wen-Li; Chen, Hui-Qin
Graphical abstract: Highlights: A phytochemical investigation on the Dendrobium nobile was performed. One new lignan (1 ) and one new fluorenone (2 ) were isolated and identified. Compounds 1 –3 showed significant α-glucosidase inhibitory activity. Molecular docking was performed to study the interactions of compounds 1 and 2 with α-glucosidase. Abstract: Two new compounds, dendronobilate (1 ) and 4- O -demethyl-nobilone (2 ), together with one known fluorenone were isolated from the aerial parts of Dendrobium nobile Lindl. Their structures were characterized by detailed analysis of 1D and 2D NMR spectra, HRESIMS and ECD spectra. Compounds 1 –3 showed significant α-glucosidase inhibitory activity with IC50 values of 27.46 ± 3.14, 4.52 ± 0.33, and 10.78 ± 2.05 μM, respectively, which were superior to the acarbose (745.9 ± 3.3 μM). The binding interactions of 1 and 2 with α-glucosidase were investigated using molecular docking simulations. In addition, compound 2 exhibited potent inhibitory effect on NO production in LPS activated RAW264.7 cells with the IC50 value of 35.40 ± 1.77 μM without cytotoxicity observed.